2011
DOI: 10.1007/s12291-011-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Antidiabetic Action of Compound GII Purified from Fenugreek (Trigonella foenum graecum) Seeds

Abstract: To study the mechanism of action of water soluble compound GII purified from fenugreek (Trigonella foenum graecum) seeds which was shown earlier to have antidiabetic effect in the subdiabetic, moderately and severely diabetic rabbits. In rabbits (1-1.5 kg bw) diabetes was induced by intravenous injection of 80 mg/kg bw of alloxan. They were fed with GII at a dose of 50 mg/kg bw daily once in the morning for 15 days in the subdiabetic and moderately diabetic and 30 days in the severely diabetic rabbits. Serum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…The protection of pancreas architecture led to an increase in insulin rate, and consequently, the regulation of glucose metabolism and an increase in body, hepatic, and renal weights (Table 1). These results, in agreement with findings recently reported by Puri et al [6]), have reported that the administration of fenugreek trigonelline to diabetic rats modulates key enzymes of metabolism such as hexokinase, glucokinase, pyruvate kinase, malic enzyme, glucose-6-phosphate dehydrogenase, glucose-6-phosphatase, sorbitol dehydrogenase, and aldose reductase, and also the glucogen rate in muscle and the liver.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The protection of pancreas architecture led to an increase in insulin rate, and consequently, the regulation of glucose metabolism and an increase in body, hepatic, and renal weights (Table 1). These results, in agreement with findings recently reported by Puri et al [6]), have reported that the administration of fenugreek trigonelline to diabetic rats modulates key enzymes of metabolism such as hexokinase, glucokinase, pyruvate kinase, malic enzyme, glucose-6-phosphate dehydrogenase, glucose-6-phosphatase, sorbitol dehydrogenase, and aldose reductase, and also the glucogen rate in muscle and the liver.…”
Section: Resultssupporting
confidence: 93%
“…One of the therapeutic approaches proposed so far for the decrease of drug-treated diabetes is based on the retardation of glucose absorption through the inhibition of carbohydrate-hydrolyzing enzymes, i.e. ; α-amylase and maltase in the intestine [6]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acarbose also decreased the blood glucose concentrations at 30 and 60 min after starch loading. In fact, previous studies have reported that administration of FSO to diabetic rats is associated with regulation of enzymes of carbohydrate metabolism such as hexokinase, glucokinase, pyruvate kinase, malic enzyme, glucose-6-phosphatase, glucose-6-phosphate dehydrogenase, aldose reductase and sorbitol dehydrogenase in liver of diabetic rats 35 .…”
Section: Discussionmentioning
confidence: 97%